Assessment of grain size and lattice parameters of titanium alloy through electromagnetic emission technique. (20th December 2011) - Chauhan, Vishal S.; Misra, Ashok
Effects of variation in grain size and lattice parameters at elevated temperatures on the electromagnetic radiation (EMR) during failure under tension of ASTM B265 Grade 2 titanium have been investigated. The EMR is observed to be anisotropic in nature. The EMR amplitude decreases with increase in grain size. The magnitude of variation depends upon the processing history of specimens. The EMR amplitude decreases exponentially with lattice parameters in titanium while the decrease in EMR frequency is polynomial in nature. The experimental results are in close agreement with the theoretical predications presented in this paper. A comparison with the results reported earlier shows that the nature of EMR responses with lattice parameters is independent of metal crystal structure. These investigations lead to a new technique for the assessment of grain size and lattice parameters in metals.